Letter from Marcia B. Booth to James Curtis Booth - Booth, Marcia B. (1886)
Marcia B. Booth, a relative of James Curtis Booth (1810-1888), writes to Booth concerning family matters.
Keywords: Booth, James Curtis, 1810-1888